The Quarter Floors - Harnum, Alan (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2020)
A piece of short fiction, loosely based on the author's own ten years of working in libraries.